2007
DOI: 10.2341/06-64
|View full text |Cite
|
Sign up to set email alerts
|

Quantity of Remaining Bacteria and Cavity Size After Excavation with FACE, Caries Detector Dye and Conventional Excavation In Vitro

Abstract: In this in vitro study, quantitative confocal microscopy was used to show differences in the quantity of bacteria remaining in dentin after excavation with different methods. A further parameter was the cavity volume after excavation relative to the original lesion size. Teeth with dentin caries were divided into three groups of 20 each. The caries was removed by a single operator using a slow handpiece and a round bur. In the first group, Fluorescence Aided Caries Excavation (FACE) was carried out: violet lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 16 publications
(19 reference statements)
1
35
0
4
Order By: Relevance
“…the PC/ IC ratio). 13,18 A relative cavity size close to 1 indicates a perfect MIP, as the volume of the removed tissue (PC) corresponds exactly to the volume of the initial carious lesion (IC volume).…”
Section: Minimal Invasiveness Potentialmentioning
confidence: 99%
See 4 more Smart Citations
“…the PC/ IC ratio). 13,18 A relative cavity size close to 1 indicates a perfect MIP, as the volume of the removed tissue (PC) corresponds exactly to the volume of the initial carious lesion (IC volume).…”
Section: Minimal Invasiveness Potentialmentioning
confidence: 99%
“…Previous studies have shown that FACE is more effective than CE in removing bacterially infected dentine. [17][18][19] Moreover, histological analysis has shown that this technology removed much more infected tissue when compared with methods based on CME and caries dye. 17 However, data on the minimal invasive potential (MIP) of FACE are scarce; only one study on the subject, which used silicone impression to measure cavity volume, has been published to date.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations